1982
DOI: 10.1128/jcm.16.5.826-831.1982
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae: comparison of respiratory tract isolates with genitourinary tract isolates

Abstract: Haemophilus influenzae isolates recovered from the genitourinary (GU) tract were shown to have a significantly different biotype distribution compared with respiratory tract isolates. Biotype IV strains were recovered more commonly from the GU tract, and most strains were non-serotypable. Antibiotic-susceptible strains isolated from the GU tract more frequently harbored plasmids of <10 megadaltons than did antibiotic-susceptible respiratory tract strains. One 2.8megadalton plasmid resident in a GU tract isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 33 publications
(35 reference statements)
2
23
1
Order By: Relevance
“…The number of reported cases has increased in the last 20 years (7,13,14,22,28). Although specific tropism of some H. influenzae strains for the genital tract has been suggested on the basis of biotyping and serotyping studies (1,18,22,28), analysis of outer membrane protein patterns and genetic characterization of isolates do not support a general concept of specific genital strains. The exception is a very homogeneous group of genital strains, usually assigned to H. influenzae biotype IV, which share singular phenotypic and genotypic characteristics (15,17,19,20,21,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The number of reported cases has increased in the last 20 years (7,13,14,22,28). Although specific tropism of some H. influenzae strains for the genital tract has been suggested on the basis of biotyping and serotyping studies (1,18,22,28), analysis of outer membrane protein patterns and genetic characterization of isolates do not support a general concept of specific genital strains. The exception is a very homogeneous group of genital strains, usually assigned to H. influenzae biotype IV, which share singular phenotypic and genotypic characteristics (15,17,19,20,21,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several authors (16,21) suggested that H. influenzae biotype IV should be considered a genital and neonatal pathogen. However, the isolation of other biotypes of these species from the genital area has been reported (1,2,13,14). Partly due to the routine use of media that do not support the growth of Haemophilus species (7) or to overgrowth by commensal microbial flora, reports of anogenital infections by H. influenza (2,14) and by H. parainfluenzae (3, 4, 18, 20;M.…”
mentioning
confidence: 99%
“…Fuzi, Letter, 1985) are sparse. The development of selective media inhibiting the less fastidious microbial flora while permitting the growth of Haemophilus species allowed a recovery rate varying between 0.2 and 5.3% (1,13,19) from colonized areas.…”
mentioning
confidence: 99%
“…Previous reports (5,9) have indicated that genitourinary strains of H . influenzae recovered from adults are predominaltly untypable and belong to biotypes 2, 3 and 4, whereas the 18 pediatric isolates from the present study were predominantly capsulated and belonged to biotypes 1 and 2.…”
Section: Haemophilus Lnfluenzae and Genital Tract Infections In Childrenmentioning
confidence: 96%